College Students’ Opinions About Coping Strategies for Mental Health Problems, Suicide Ideation, and Self-Harm During COVID-19 - Klonoff-Cohen, Hillary (Frontiers in Psychology, 2022)
Background Mental health problems have emerged as a significant health complication in United States colleges during COVID-19, and as a result, they have been extensively investigated in the United States and internationally. In contrast, research on coping among the college population during the pandemic is scant. Hence, this study investigated coping strategies proposed by undergraduate students attending a Midwestern university. Objectives The purpose of this preliminary study was to obtain college students’ feedback/opinions about coping strategies for mental health problems, suicide ideation, and self-harm during COVID-19. Methods In December 2021, one-hundred and four undergraduate students (ages 18–22 years) completed an online survey on coping strategies using Qualtrics. Major topics included: (1) Types of coping strategies/styles expressed by students for general mental health problems, (2) Types of coping strategies for suicide ideation and self-harm behaviors, (3) Preferred platforms for receiving coping therapy, and (4) Reasons for accepting or refusing parent involvement with mental health problems. Results The most beneficial coping strategies for mental health were ranked by college students as follows: (1) a skills training development program (30%), (2) meditation (19%), and (3) mindfulness exercises (15%), and physical education (11%). The respondents’ best coping strategies for preventing self-harm and suicide ideation/behaviors during COVID-19 were ranked as: (1) improving support from friends (32%), (2) building self-esteem (29%), and (3) addressing anger, depression, stress, and loneliness (25%). Finally, a total of 50% of participants felt that parents should be involved in college student interventions. Students stated that the most important type of support that they received from their parents were: (1) emotional support (31%), (2) direction and/or assistance with solutions (27%), and problem-solving (16%). Conclusion This study identified potential avenues which could be implemented into action during future outbreaks. Specifically, employing interventions that: (i) train undergraduate students to employ more effective skills training coping strategies or practicing mindfulness or meditation; (ii) integrate mental health, suicide, and self-harm prevention into the curriculum; (iii) offer more in-person campus services targeted toward the psychological and emotional effects of a pandemic, and (iv) involve support persons (e.g., family) in students’ lives to enhance their well-being during and after COVID-19.